Analysis of Agricultural Potential Counseling Strategies Through Independent Thematical Real Work College Learning Independent Campus STIE Bima Activities - Muniarty, Puji; Rimawan, M; Wulandari; Abal Karima; Ovriyadin; Hubeis, Musa (Yayasan Ilomata, 2024)
Technology adoption is a process in which business actors and farmers have the initiative to participate or be actively involved in innovative activities in the management and utilization of agricultural products. This phenomenon indicates the need for a special strategy in optimizing the utilization of agricultural products. Researchers identify strategic problems/issues through the results of analysis during field observations. After each variable is rated and weighted according to the criteria, it can be concluded that the opportunity value of 2.14 is greater than the threat value of 0.9. If the difference is obtained, the opportunity value is 1.24 (y) greater than the threat of implementing agricultural potential development counseling through KKN activities. Based on an analysis of the implementation of agricultural extension to develop agricultural potential through KKN activities, three strategies were found, namely Collaboration of agricultural extension assistance with innovators, extension assistance in convincing MSME groups to demonstrate technology implementation, and MSME assistance supported by innovation and technology application.